2005
DOI: 10.1038/sj.ijo.0802884
|View full text |Cite
|
Sign up to set email alerts
|

Insulin determines leptin responses during a glucose challenge in fed and fasted rats

Abstract: OBJECTIVE: Leptin secretion has been shown to respond acutely to changes in blood glucose and insulin. Nutritional state also has a marked effect on both the level of circulating leptin protein and leptin gene expression. The aim of this study was to assess whether the prior nutritional state altered the leptin secretory response to an acute glucose challenge, and to determine potential mechanisms. DESIGN: Male fed or fasted rats (200-250 g) were administered a single intravenous glucose bolus (1, 4 or 7 g/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 41 publications
5
20
0
Order By: Relevance
“…Furthermore, we show that, in addition to the maintaining "basal" or spontaneous release of leptin over the long term, insulin can acutely stimulate the rate of release of preformed (biosynthetically labeled) leptin, as we have previously observed in rat adipose tissue (16). Thus, our data suggest that the insulin stimulation of leptin secretion from a stored intracellular pool may contribute to meal-induced variations in serum leptin levels that are documented in humans as well as rats (3,18,35,36).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, we show that, in addition to the maintaining "basal" or spontaneous release of leptin over the long term, insulin can acutely stimulate the rate of release of preformed (biosynthetically labeled) leptin, as we have previously observed in rat adipose tissue (16). Thus, our data suggest that the insulin stimulation of leptin secretion from a stored intracellular pool may contribute to meal-induced variations in serum leptin levels that are documented in humans as well as rats (3,18,35,36).…”
Section: Discussionsupporting
confidence: 78%
“…Walker et al (35) found that administration of glucose caused a prompt increase in serum leptin, independent of alterations in leptin mRNA, in fed rats with higher adipose tissue leptin content but not in fasted rats with low adipose tissue leptin content. In addition, the magnitude of ultradian leptin pulses is greater in obese than in lean humans (36), and this could be related to their larger stores of preformed leptin.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Intracellular leptin was decreased by fasting in isolated rat adipocytes, and this has previously been shown in rat epididymal adipose tissue. 1,24 Thus, both before and during the incubation, the adipocytes of fed rats had an increased capacity to secrete leptin in response to nutritional stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Serum leptin responses in fasted rats correlated with a suppressed serum insulin response to the glucose challenges in fasted rats and in the fed rats the leptin response was also governed by the serum insulin. 1 The aim of the current study was to determine if incubation with high insulin and glucose concentrations could reverse the suppression of leptin secretion in adipocytes isolated from fasted rats. As glucose uptake into adipocytes has also been associated with leptin secretion, 12 we examined the role of insulin-regulated glucose metabolism as a mechanism for the observed nutritional regulation of leptin expression, production and secretion.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation